A Noninvasive Approach to Assess the Prevalence of and Factors Associated With Anemia Risk in Malaysian Children Under Three Years of Age: Cross-Sectional Study - Muhammad Yazid Jalaludin; Ho Bee Kiau; Suriati Hasim; Wai Khew Lee; Angie Low; Nik Harlina Nik Kazim; Jia Tse Hoi; Sri Wahyu Taher (JMIR Pediatrics and Parenting)
Abstract BackgroundAnemia remains a significant public health concern with adverse effects among children. Noninvasive screening assessments enable the early detection and prompt treatment of anemia. However, there is limited literature on the use of such screening assessments. ObjectiveThe study aimed to assess the prevalence of and factors associated with being at risk of anemia among Malaysian children aged ≥6 months to ≤36 months by using a noninvasive hemoglobin assessment. MethodsThis was a cross-sectional study (from July to December 2022) of outpatient Malaysian children, aged ≥6 months to ≤36 months, who were selected from five maternal-and-child health clinics by convenience sampling. At risk of anemia was defined as a total hemoglobin level of <12 g/dL, measured using the Masimo Rad-67, a noninvasive screening device for total hemoglobin levels. The χ2 ResultsThe study included 1201 participants, of whom 30% (95% CI 28‐33) were at risk of anemia. Children aged 6‐12 months (210/364, 57.7%, PPPPPP ConclusionsThe current study revealed a substantial prevalence of Malaysian children being at risk of developing anemia. The study results therefore imply a need for more community education and awareness on anemia, including nutrition education, as well as targeted community screening to enable the early detection and prompt treatment of anemia cases. Anemia reduction strategies in Malaysia should consider the highlighted factors indicative of higher risk of anemia.